2017
DOI: 10.1186/s12902-017-0217-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of trace metal elements with lipid profiles in type 2 diabetes mellitus patients: a cross sectional study

Abstract: BackgroundIt is well known that dyslipidemia and chronic hyperglycemia increase the onset of diabetes and diabetic complication. The aim of this study is to see the association of trace metals elements and lipid profile among type 2 diabetes mellitus patients.MethodsThe study was conducted on 214 type 2 diabetic patients at Jimma University Specialized Hospital, Jimma, Ethiopia. All the eligible study participants responded to the structured interviewer administered questionnaire and fasting venous blood was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 50 publications
(45 reference statements)
2
17
2
2
Order By: Relevance
“…The diabetics were characterised by inverse correlation between the serum total cholesterol and serum Zn levels and positive the serum Cu/Zn ratio. Similarly, Wolide et al [ 55 ] found negative correlations between the serum Zn and Fe levels and the total and LDL, the serum Zn and triacylglycerol levels.…”
Section: Discussionmentioning
confidence: 86%
“…The diabetics were characterised by inverse correlation between the serum total cholesterol and serum Zn levels and positive the serum Cu/Zn ratio. Similarly, Wolide et al [ 55 ] found negative correlations between the serum Zn and Fe levels and the total and LDL, the serum Zn and triacylglycerol levels.…”
Section: Discussionmentioning
confidence: 86%
“…It must also be stressed that there might be a different availability of a metal, starting from its entry into cells. In fact, a negative correlation has been demonstrated in the serum levels of trace metals and lipid metabolism products (cholesterol, triglycerides, lipoproteins) [62].…”
Section: Discussionmentioning
confidence: 99%
“…Trace element associated antioxidant enzymes are altered in diabetes [ 7 ]. Many cohort studies have shown that the homeostasis of trace elements can be altered with diabetes mellitus [ 8 ]. Early imbalances in specific elements may play an important role in disrupting insulin metabolism [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%